Successful recovery from COVID‐19 in three kidney transplant recipients who received convalescent plasma therapy. Issue 1 (3rd September 2020) - Naeem, Syed; Gohh, Reginald; Bayliss, George; Cosgrove, Christopher; Farmakiotis, Dimitrios; Merhi, Basma; Morrissey, Paul; Osband, Adena; Bailey, Jeffrey A.; Sweeney, Joseph; Rogers, Ralph
Abstract: Novel coronavirus disease 2019 (COVID‐19) is a highly infectious, rapidly spreading viral disease that typically presents with greater severity in patients with underlying medical conditions or those who are immunosuppressed. We present a novel case series of three kidney transplant recipients with COVID‐19 who recovered after receiving COVID‐19 convalescent plasma (CCP) therapy. Physicians should be aware of this potentially useful treatment option. Larger clinical registries and randomized clinical trials should be conducted to further explore the clinical and allograft outcomes associated with CCP use in this population.